The relationship between psychological capital and humanistic caring ability among mental health nurses in Saudi Arabia - Atallah Alenezi; Fahad M. Alhowaymel; Abdulaziz F. Abaoud; Mona Hamdy Mostafa (BMC, 2024)
Abstract Background The ability to provide humanistic care has a significant impact on the therapeutic relationships in psychiatric services, which in turn influences patients' outcomes. Aim To examine the relationship between psychological capital and humanistic care ability among mental health nurses in Saudi Arabia. Methods A descriptive correlational research design was implemented in this study. A convenience sampling method was used to collect information from 500 mental health nurses from a governmental mental health facility. The data were collected using the psychological capital questionnaire and the caring ability inventory. Results The results revealed high levels of psychological capital and humanistic care ability among mental health nurses. Psychological capital significantly predicted humanistic care ability ( $$\:R^{2}=$$ 0.630, F(1,498) = 851.16, p< 0.001). Also, there were significant relationships between sociodemographic variables and psychological capital (age, educational level, and professional title) and humanistic care ability (age and years of experience). Conclusion Psychological capital was found to be be positively associated with the humanistic care ability of mental health nurses. The findings of this study suggest that nursing managers should explore strategies from the viewpoint of positive psychology to enhance the psychological capacity of mental health nurses to provide humanistic care abilities, which can effectively improve nurses-patients' relationships and outcomes in clinical practice.